Strategy for Safe Passenger Transport during the COVID-19 Pandemic: From Review to Recommendation - Retno Rusdjijati; Sumarno Adi Subrata; Zulfikar Bagus Pambuko; Muji Setiyo; Marcin Noga (Automotive Experiences, 2022)
The COVID-19 pandemic caused a large-scale disruption to countries worldwide particularly in road traffic changes and people mobility. To respond to this, a titanic amount of published studies had investigated those concerns. However, a study describing mitigation efforts relating to this pandemic in the transportation sector is scarce. On the other hand, the lack of coordination between transportation authorities, public transport operators, and passengers triggers complex issues including the accumulation of passengers at bus stations that potentially increase virus transmission. For this reason, this article intends to investigate and establish strategies for safe passenger transport. The finding of the article presented four basic strategies as follows: First, a coordinated response among stakeholders and government is needed to develop comprehensive policies. Second, coordinated demand management is required to maintain a balance between government policies and citizen demands. Third, provide health education on Personal Protective Equipment (PPE) to public transport crews. Fourth, protecting the passengers and maintaining trust in public transport services. Additionally, it is recommended to provide adequate infrastructure, perform regular check-ups (i.e. assessing body temperature before entering public transportation), provide up-to-date COVID-19 health alert, and implement health protocol. Also, when this pandemic is over, the use of fuel-based transportation needs to be reduced, especially for short trips. To optimize this strategy, the role of government and health authorities on the policy side is crucial. Also, a good response from public transport operators and passengers is the key to defeat the COVID-19 pandemic in the transportation area.